A precise photometric ratio via laser excitation of the sodium layer – I. One-photon excitation using 342.78 nm light. Issue 3 (7th June 2021) - Albert, Justin E; Budker, Dmitry; Chance, Kelly; Gordon, Iouli E; Pedreros Bustos, Felipe; Pospelov, Maxim; Rochester, Simon M; Sadeghpour, H R
ABSTRACT: The largest uncertainty on measurements of dark energy using type Ia supernovae (SNeIa) is presently due to systematics from photometry; specifically to the relative uncertainty on photometry as a function of wavelength in the optical spectrum. We show that a precise constraint on relative photometry between the visible and near-infrared can be achieved at upcoming survey telescopes, such as at the Vera C. Rubin Observatory, via a laser source tuned to the 342.78 nm vacuum excitation wavelength of neutral sodium atoms. Using a high-power laser, this excitation will produce an artificial star, which we term a 'laser photometric ratio star' (LPRS) of de-excitation light in the mesosphere at wavelengths in vacuum of 589.16, 589.76, 818.55, and 819.70 nm, with the sum of the numbers of 589.16 and 589.76 nm photons produced by this process equal to the sum of the numbers of 818.55 and 819.70 nm photons, establishing a precise calibration ratio between, for example, the r and z filters of the LSST camera at the Rubin Observatory. This technique can thus provide a novel mechanism for establishing a spectrophotometric calibration ratio of unprecedented precision for upcoming telescopic observations across astronomy and atmospheric physics; thus greatly improving the performance of upcoming measurements of dark energy parameters using type SNeIa. The second paper of this pair describes an alternative technique to achieve a similar, but brighter, LPRS than the technique described in this paper, by using two lasers near resonances at 589.16 and 819.71 nm, rather than the single 342.78 nm on-resonance laser technique described in this paper.